Antimicrobial Resistance Surveillance of Skin and Soft Tissue Infections: Hospital-Wide Bacterial Species and Antibiograms to Inform Management at a Zonal Tertiary Hospital in Mwanza, Tanzania - Justine BN; Mushi MF; Silago V; Igembe Z; Muyombe J; Kishengena PP; Michael Jnr NS; Maganga MG; Massenga A; Tegete F; Massaga FA; Seni J (Infection and Drug Resistance)
Baraka N Justine,1 Martha F Mushi,1 Vitus Silago,1 Zechariah Igembe,2 John Muyombe,2 Peter Peter Kishengena,2 Nyanda Shango Michael Jnr,2 Mathew Gabriel Maganga,3 Alicia Massenga,4,5 Francis Tegete,6 Fabian A Massaga,5,7 Jeremiah Seni1,2 1Department of Microbiology and Immunology, Weill-Bugando School of Medicine, Catholic University of Health and Allied Sciences, Bugando, Mwanza, Tanzania; 2Clinical Microbiology Unit, Central Pathology Laboratory, Bugando Medical Center, Mwanza, Tanzania; 3Department of Pharmacy and Quality Assurance Unit, Bugando Medical Center, Mwanza, Tanzania; 4Department of Pediatric Surgery, Bugando Medical Center, Mwanza, Tanzania; 5Department of General Surgery, Catholic University of Health and Allied Sciences, Bugando, Mwanza, Tanzania; 6Department of Plastic and Reconstructive Surgery, Bugando Medical Center, Mwanza, Tanzania; 7Department of General Surgery, Bugando Medical Center, Mwanza, TanzaniaCorrespondence: Jeremiah Seni, Department of Microbiology and Immunology, Weill-Bugando School of Medicine, Catholic University of Health and Allied Sciences, P.O. Box 1464, Bugando, Mwanza, Tanzania, Tel +255 784 593000, Email senijj80@gmail.comPurpose: The National Action Plan on antimicrobial resistance (NAP-AMR) in Tanzania is focused on blood stream infections and urinary tract infections despite skin and soft tissue infections (SSTIs) being common. This study assessed the proportion of laboratory-confirmed SSTIs, identify bacterial species involved, analyze AMR phenotypes, and investigate the risk factors associated with multidrug-resistant (MDR) SSTIs.Patients and Methods: Analytical cross-sectional study was conducted between January and June 2023, involving 614 patients with SSTIs. Patients’ information was collected using standard AMR surveillance tools, and either pus swabs or pus aspirate or necrotic tissues were collected and analyzed using standard microbiological procedures, WHONET and STATA software programs.Results: The median age (interquartile range) of patients was 34 (14– 54) years with males accounting for 54.4%. Laboratory-confirmed SSTIs was 72.5% (445/614), yielding 586 bacterial isolates. The most frequent SSTIs types were surgical site infections (30.0%), chronic wounds (27.9%), and traumatic wounds (19.7%). The commonest pathogens were Staphylococcus aureus (17.1%), Escherichia coli (17.1%), and K. pneumoniae (16.0%). The AMR phenotypes identified were methicillin resistant Staphylococcus aureus, 29.0%; Extended-spectrum beta lactamase producing Gram-negative bacteria, 47.3%; and carbapenem resistant Gram-negative bacteria, 12.9%. The overall MDR SSTIs was 40.9% (251/614) and was significantly higher among inpatients compared to outpatients [OR (95% CI); p-value: 1.86 (1.33– 2.59); p-value< 0.001].Conclusion: Approximately three-quarter of patients have laboratory-confirmed SSTIs caused predominantly by MDR pathogens. Revisiting SSTIs treatment guidelines at BMC and inclusion of SSTIs in the on-going AMR surveillance in Tanzania are recommended.Plain Language Summary: Tanzania National Action Plan on combating resistant bugs is exclusively focused on urinary tract infections and blood stream infections despite enormous impact conferred by skin and soft tissue infections.Bugs which are resistant to commonly used antibiotics were found more among patients admitted in the hospital in contrast to those attending outpatient clinics.This study highlights a pressing need to develop treatment guidelines based on generated local research-evidence to foster favorable patients’ outcomes.Keywords: skin and soft tissue infections, antimicrobial resistance, surveillance, Tanzania